2013
DOI: 10.1182/blood-2013-01-474916
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the Ikzf1 locus

Abstract: Key Points Multiple enhancers identified at the Ikzf1 locus with shared and distinct epigenetic and transcriptional properties. Transcription factor networks that distinguish between LMPP-specific and T cell–specific Ikzf1 enhancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Interestingly, the later set of genes contained multiple active enhancers within their gene bodies in DKO1 cells, and these same enhancers were methylated in HCT116 cells. Intronic enhancers have been previously described to regulate the genes they reside within [23,[31][32][33]. Here, we have identified several hundred genes that may be controlled by increases in active histones at intragenic enhancers.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the later set of genes contained multiple active enhancers within their gene bodies in DKO1 cells, and these same enhancers were methylated in HCT116 cells. Intronic enhancers have been previously described to regulate the genes they reside within [23,[31][32][33]. Here, we have identified several hundred genes that may be controlled by increases in active histones at intragenic enhancers.…”
Section: Discussionmentioning
confidence: 86%
“…Ikzf1 enhancers feature enrichment sites for several key transcriptional regulators of the hematopoietic and lymphoid system. Occupancy of Ikzf1 enhancers by the Ebox proteins (E2A and HEB), RUNX1, and TCF-1 indicates that these may contribute to IKAROS induction in the HSCs, with changes in their expression likely contributing to changes in Ikzf1 transcription during differentiation (Yoshida et al 2013). Still, it remains unclear whether and how these factors impact Ikzf1 expression.…”
Section: Expression and Immune Cell Phenotypesmentioning
confidence: 99%
“…IKAROS (Ikzf1) is strongly expressed from the HSCs to mature T and B effector cells and is the only family member that is necessary at both the onset and later stages of lymphocyte differentiation. There is an extensive redundancy of regulatory elements at the Ikzf1 locus, with two promoters and six enhancers providing locus control region activity during hemolymphopoiesis (Yoshida et al 2013;Perotti et al 2015). Ikzf1 enhancers feature enrichment sites for several key transcriptional regulators of the hematopoietic and lymphoid system.…”
Section: Expression and Immune Cell Phenotypesmentioning
confidence: 99%
“…Mouse studies suggest that the transcription of IKZF1 during normal hematopoiesis is regulated by a complex network. 18 However, Ikaros protein is expressed at high levels in most hematopoietic cells, and posttranslational modifications are hypothesized to play a critical role in regulating Ikaros activity. 19 Several groups have shown that phosphorylation, [19][20][21][22][23][24] sumoylation, 25 and ubiquitination 22 can regulate Ikaros function as a transcriptional repressor.…”
Section: Introductionmentioning
confidence: 99%